Learning Styles and the Use of ICT in University Students within a Competency-Based Training Model - Sergio Humberto Barbosa Granados; Marlly Leana Amariles Jaramillo (Springer, 2019)
The purpose of the study was to determine the learning styles (LS) and the use of Information and Communication Technologies (ICT) in university students within a competency-based training model, as well as to identify possible differences related to the frequency of use of ICT in terms of gender. A descriptive and correlational quantitative approach was applied with a non-experimental and transversal design. The study used an intentional non-probabilistic sample of 113 students in undergraduate psychology, public accounting and business administration programs that use a competency-based model at a private Colombian university. The outcome showed no significant differences among LS or in the frequency of ICT use in students with competency-based training. Additionally, the outcome showed a gender gap in